Harry Potter and beyond : on J. K. Rowling's fantasies and other fictions - Pugh, Tison (University of South Carolina Press, 2020)
"Harry Potter and Beyond explores J. K.Rowling's beloved best-selling series and its virtuoso reimagining of British literary traditions. Weaving together elements of fantasy, the school-story novel, detective fiction, allegory, and bildungsroman, the Harry Potter novels evade simplistic categorization as children's or fantasy literature. Along with the seven foundational novels of the Harry Potter series, Harry Potter and Beyond assesses the extraordinary range of supplementary material concerning the young wizard and his allies, including the films of the books, the subsequent film series, and a range of other Potter-inspired narratives. Beyond the world of Potter, Pugh surveys Rowling's literary fiction The Casual Vacancy and her detective series featuring Cormoran Strike, written under the pseudonym Robert Galbraith. Through this comprehensive overview of Rowling's body of work, Pugh reveals the vast web of connections between yesteryear's stories and Rowling's vivid creations"--